Tobin's Q Modeling Through the Du Pont System Financial Performance Method Using SEM-PLS - Yulandri, Elsa; Hertina, Dede; Asih, Vemy Suci (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This study aims to examine the factors that influence Tobin's Q. This goal is achieved by testing the Debt to Equity Ratio (DER), Dividend Yield, and Firm Size through the financial performance mediating variable using the du Pont system method. This study uses a population of 20 companies indexed in the High Dividend Index of the Indonesia Stock Exchange with a saturated sample technique. The 20 companies are the samples in this study. This research approach uses descriptive quantitative that is path analysis to test the hypothesis that has been formed. The most important research result is that the financial performance of the du Pont system method affects mediating the Debt to Equity Ratio (DER) and Firm Size of Tobin's Q. Then, partially Dividend Yield and Financial Performance of the du Pont system method significantly influence the company's Tobin's Q. High Dividend Index 20